Balanced Scorecard approach for benchmarking Rural ICT Projects - K.M., Nazri; Tariq, Zaman; M.O., Rosita (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The contribution of Information Communication Technologies (ICTs) is significant in rural development especially to bridge the digital divide. However the ICT projects in rural communities are confronted with challenges of performance management, access to infrastructure, limited formal education, insufficient training and capacity building, financial and political constraints, and social and cultural challenges. To overcome these challenges the organizations focus on strategic planning and constant performance measurements. The Balanced Scorecard is a performance measurement system that supplements traditional financial measures from three additional perspectives: customer perspective, internal business perspective and innovation and learning perspective. In the paper we explore the modified Balanced Scorecard for rural ICT projects and discuss the monetary and non- monetary issues that affect the performance of ICT projects in rural communities. We also examine the strategic process of designing and implementing the project on the base of Balanced Scorecard approach. This paper will highlight some of the lessons learnt during our replication and deployment process of the project using the eBario Project as an initial guide.